Investigating Constraints to Poultry Management Practices among Smallholder Farmers in Benue State, Nigeria - Mbah, Evangeline (International Journal of Sustainable Agricultural Research, 2018)
The study was carried out to assess poultry management practices among smallholder farmers in Benue state, Nigeria. Questionnaire was used to collect data from a sample of 80 respondents used for the study. Descriptive statistics such as frequency, percentage, mean score as well as inferential statistics which include factor analysis and logit regression were used for data analysis. Results revealed that 56.7% of the respondents were between the ages of 21 and 40 years, 47.5% had household size of 6-10 persons, 88.6% were literate having 1-10 years of farming experience (93.8%). Findings also show that 48% of the respondents practiced intensive system of poultry while 41.3% of them indicated that major reason for choice of poultry management system is because it is cheap/less expensive. Types of poultry management practices include proper sanitation (80%), cull sick birds (76.3%), brooding of chicks (73.8%) and use disinfectants (70%). Results further indicate constraints to poultry management which include technical, labour and input related factors. The study recommends that efforts are needed in promoting increase in poultry production through adequate pests and diseases control to enhance productivity.